PERANCANGAN SISTEM INFORMASI PEMBUKUAN PERTANIAN DI DESA SUKAMAKMUR - Mochamad Ardiansyah (2023)
Looking at the background, there are still many Sukamakmur villagers who do business without computerized financial records. then identified some of the problems found, namely how to create a bookkeeping information system to record data, facilitate financial records, and monitor financial records. With the aim of facilitating agricultural business actors in financial records and helping display news in the agricultural sector.In this study, researchers used several steps used in making this application, namely data collection, making an application which consisted of several stages, the first stage was the Needs Analysis stage, system design, design, implementation and testing stage. In making the accounting and learning android application, the researcher uses the waterfall method in system design. Based on the background of Sukamakmur Village, where the system works on bookkeeping in Sukamakmur village, it is done manually, the process implementation is still quite difficult because some people still have little knowledge about bookkeeping, starting from making and memorizing certain formulas, a system was designed that makes it easy to make income reports sequentially based on android and website.From Haris's research, it was concluded that bookkeeping and learning applications are described using UML in making system designs, applications that make it easier for communities or companies to perform calculations and store data, communities and village heads can connect in real time with web servers and applications, and village heads can save reports and download accounting user reports, so you can see income in the village.